Mitochondrial phosphoenolpyruvate carboxykinase (PEPCK-M) and serine biosynthetic pathway genes are co-ordinately increased during anabolic agent-induced skeletal muscle growth - Brown, David M.; Williams, Hannah; Ryan, K.J.P.; Wilson, T.L.; Daniel, Zoe C.T.R.; Mareko, M. H. D.; Emes, Richard D.; Harris, D. W.; Wattis, Jonathan A.D.; Dryden, Ian L.; Hodgman, T. C.; Brameld, John M.; et al. (Nature Publishing Group, 2016)
We aimed to identify novel molecular mechanisms for muscle growth during administration of anabolic agents. Growing pigs (Duroc/(Landrace/Large-White)) were administered Ractopamine (a beta-adrenergic agonist; BA; 20ppm in feed) or Reporcin (recombinant growth hormone; GH; 10mg/48hours injected) and compared to a control cohort (feed only; no injections) over a 27-day time course (1, 3, 7, 13 or 27-days). Longissimus Dorsi muscle gene expression was analyzed using Agilent porcine transcriptome microarrays and clusters of genes displaying similar expression profiles were identified using a modified maSigPro clustering algorithm.